Anticoccidial activities of Piper betle L essential oil on Eimeria tenella oocysts - Rina Ristanti; Penny Humaidah Hamid; Herjuno Ari Nugroho; Tri Rini Nuringtyas; Syahputra Wibowo; Pamungkas Rizki Ferdian; R. Lia Rahadian Amalia; Tamara Munoz Caro; Shelly Kusumarini; April Hari Wardhana; Makoto Matsubayashi (Scientific Reports)
Abstract Coccidiosis poses a significant threat to the poultry industry, with synthetic antibiotics and disinfectants being the primary tools for control. This study investigated the potential of Piper betle L essential oil (PBEO) as a natural alternative against Eimeria tenella, one of the most pathogenic Eimeria species affecting poultry. Our findings revealed that PBEO exhibits significant anticoccidial effects through two primary mechanisms: (i) oocysticidal activity by disintegrating oocyst walls and (ii) inhibition of the sporulation process. PBEO demonstrated oocysticidal activities ranging from 8.67 to 95.33% across concentrations from 0.04 to 40%. Notably, at 72 h post-incubation, a 0.04% PBEO concentration significantly reduced the number of sporulated oocysts (P ≤ 0.05) to 71.67%, showing effects comparable to those of formalin. PBEO reduced 50% of oocyst sporulation (IC50) in the concentration of 1.31% at 72 h. Gas chromatography-mass spectrometry (GC-MS) identified the primary constituents of PBEO, including eugenol, beta-caryophyllene, and other key compounds, collectively constituting 96% of the oil. This research underscores the potential of PBEO as a natural anticoccidial agent and lays the groundwork for further studies aimed at identifying, isolating, and developing active compounds that may specifically target the sporogony process in coccidian parasites.